2015
DOI: 10.3766/jaaa.26.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hearing Impairment in Older Adults on Communication Partners: A Systematic Review

Abstract: This review highlights the broad effects of hearing impairment and the importance of involving CPs in hearing loss treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 62 publications
5
68
0
2
Order By: Relevance
“…The NCOA study, over a decade old, helped establish the need for better understanding of the impact and role of communication partners in their loved one's evaluation and treatment decisions. In a 2015 systematic review on the effects of hearing impairment on communication partners, Kamil and Lin (2015) concluded that communication partners of the hard of hearing experience a restricted social life, increased communication burden, poorer quality of life, and decreased relationship satisfaction, and that treatment of hearing loss can improve these issues. Although previous research has established the effects of hearing impairment on communication partners, this study aims to expand our knowledge in this area by determining how communication partners may influence the hearing help-seeking behavior of a person with hearing impairment.…”
Section: Hearing Loss and Health Behaviormentioning
confidence: 99%
“…The NCOA study, over a decade old, helped establish the need for better understanding of the impact and role of communication partners in their loved one's evaluation and treatment decisions. In a 2015 systematic review on the effects of hearing impairment on communication partners, Kamil and Lin (2015) concluded that communication partners of the hard of hearing experience a restricted social life, increased communication burden, poorer quality of life, and decreased relationship satisfaction, and that treatment of hearing loss can improve these issues. Although previous research has established the effects of hearing impairment on communication partners, this study aims to expand our knowledge in this area by determining how communication partners may influence the hearing help-seeking behavior of a person with hearing impairment.…”
Section: Hearing Loss and Health Behaviormentioning
confidence: 99%
“…Other studies used quantitative methods such as questionnaires. In terms of hearing assessment, Kamil and Lin (2015) also found that the study participant’s hearing was tested and reported using a number of different methods such as pure-tone audiometry, speech recognition tests, and participant self-report. Due to the heterogeneity across studies, a meta-analysis could not be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Progression in hearing loss cannot be remediated; therefore, optimal management of this condition not only requires early recognition and rehabilitation, but it also should include an evaluation of QoL status and its assessment [19][20][21][22] . According to the study by patients reporting hearing loss shows weak correlation each other, so we need new scales to asses the subjects with hearing loss 24 .…”
Section: Discussionmentioning
confidence: 99%